2002
DOI: 10.1556/avet.50.2002.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A contamination of cereal grains and coffee in Hungary in the year 2001

Abstract: Ochratoxin A (OTA) is a nephrotoxic and carcinogenic mycotoxin, a secondary metabolite produced by mould fungi belonging to several Aspergillus and Penicillium species. It is formed during the storage of cereal grains and other plant-derived products. OTA ingested by humans and animals with the food or feed may exert deleterious effects on health. The purpose of this study was to investigate the ochratoxin contamination of the most important potential sources of OTA. The OTA content of cereal samples for human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…OTA contamination level exceeded largely the maximum limit set in the EU regulation (5 lg/kg) (Commission Regulation EC, 2002 in 38% of positive wheat samples (Table 1). The contamination of wheat or derived products by OTA is a worldwide problem (Czerwiecki, Czajkowska, & Witkowska-Gwiazdowska, 2002;Fazekas, Tar, & Zomborszky-Kovacs, 2002;Speijers & Van Egmond, 1993;Tangni & Pussemier, 2006;Trucksess, Giler, Young, White, & Page, 1999), however, countries surrounding the Mediterranean Sea presented high levels of OTA contamination, such as Morocco (Zinedine et al, 2006), Italy (Solfrizo et al, 1998) and Spain (Araguas et al, 2005). In Tunisia, wheat contamination by OTA seems to be higher.…”
Section: Ota In Wheatmentioning
confidence: 99%
“…OTA contamination level exceeded largely the maximum limit set in the EU regulation (5 lg/kg) (Commission Regulation EC, 2002 in 38% of positive wheat samples (Table 1). The contamination of wheat or derived products by OTA is a worldwide problem (Czerwiecki, Czajkowska, & Witkowska-Gwiazdowska, 2002;Fazekas, Tar, & Zomborszky-Kovacs, 2002;Speijers & Van Egmond, 1993;Tangni & Pussemier, 2006;Trucksess, Giler, Young, White, & Page, 1999), however, countries surrounding the Mediterranean Sea presented high levels of OTA contamination, such as Morocco (Zinedine et al, 2006), Italy (Solfrizo et al, 1998) and Spain (Araguas et al, 2005). In Tunisia, wheat contamination by OTA seems to be higher.…”
Section: Ota In Wheatmentioning
confidence: 99%
“…Its occurrence has been reported in cereal grains, coffee beans, nuts, wine, pork, beer, cheese and several spices (Fazekas et al, 2002;Studer-Rohr et al, 1995;Van Egmond and Speijers, 1994). A number of studies have suggested a role for OTA in the development of several types of cancer (Reijula and Tuomi, 2003;Schwartz, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It also occurs in maize, rice, peas, beans and cowpeas; developing country origins of ochratoxin A include Brazil, Egypt, Chile, Senegal, Tunisia, Nigeria, India and Indonesia (Wild and Hall, 2000). The ability of OA to transfer from animal feeds to animal products has been demonstrated by the occurrence of this toxin in retail pork products, and the blood of pigs in Europe (Fazekas et al, 2001;Friensen et al, 2008). It has been suggested that pork products are a significant human dietary source of OA which has been found in blood (and milk) from individuals in a variety of European countries, such as France, Italy, Germany, Dewnmark, Sweden, Poland the former Yugoslavia, and Bulgaria ( Abarca et al, 2001)).…”
Section: Ochratoxin Amentioning
confidence: 99%